PERANAN LEVERAGE KEUANGAN, UKURAN, PROFITABILITAS, DAN TIPE KEPEMILIKAN PERUSAHAAN TERHADAP PENGUNGKAPAN SUKARELA PERUSAHAAN DALAM MEDIA INTERNET - PRISCILLIA TEDJO, PAULINE (Berkala Ilmiah Mahasiswa Akuntansi)
Internet media is media that is easily spread and accessible, not knowing the limits, can mengefesiensikan cost and time to provide information in the field of economics and business in particular to convey the information of financial and non financial company to its stakeholders and other users who need due. Disclosure practices in this Internet medium called the Internet Financial Reporting (IFR). Some of the variables that play a role in the company's voluntary disclosure in the media including the internet financial leverage, firm size, profitability, corporate status and corporate performance. From the results of the discussion can be concluded that (1) companies that have a high degree of financial leverage will disclose more financial information to divert the attention of stakeholders in addition to improving the performance of the company to refund obligations, (2) the size of the company's influence on the larger company then the company will voluntarily mengunkapkan more company information, (3) the higher the level of profitability will add value to the company and other stakeholders, (4) types of influence corporate ownership as an indicator of a company that will make voluntary disclosure.